The Lessons of Mumbai - Rabasa, Angel; Blackwill, Robert D.; Chalk, Peter; Cragin, Kim; Fair, C. Christine (RAND Corporation, 2023)
This study of the Mumbai, India, terrorist attack of November 2008 identifies the operational and tactical capabilities displayed by the terrorists and evaluates the response of the Indian security forces, with the goal of helping counterterrorism authorities in India and elsewhere to prepare for or counter future terrorist attacks on urban centers.